Applying trading workshops for improving the oral skill in the English Language for the Amazon ecotourism - Huaca Franco, Brayan Johao; López López, Jacqueline Elizabeth; Bonilla Tenesaca , Josue Reinaldo (SATHIRI, 2025)
This research addressed the linguistic barriers faced by ecotourism providers in Cascales, Sucumbíos, with a focus on improving their English communication skills. The study evaluated whether specific workshops could improve these skills, thereby increasing tourist satisfaction and generating greater economic and educational benefits. A quasi-experimental methodology was used, which included pre- and post-workshop surveys, interviews, and focus group discussions with a sample of 14 local providers selected for their basic proficiency in English. The results revealed that, while some providers showed confidence in their English communication skills, there was considerable variability in their effectiveness. Specifically, 21% of participants reported difficulties in effectively communicating with tourists, and many-faced significant challenges related to intonation, pronunciation, and fluency. Although participants showed a high level of interest in the training workshops and were willing to seek feedback, their inconsistent focus on improving oral skills limited the overall impact of the training. The study concluded that existing training programs did not fully address the specific needs of the region's ecotourism sector. It is recommended that future research explore the longitudinal impacts of training interventions, consider cultural and contextual factors that influence language learning, and examine alternative methods for improving language skills. This would contribute to a more successful and sustainable ecotourism model in Cascales.
Keywords: Ecotourism; Communication Skills; Training Workshops